Comissões da Verdade no Brasil e trabalhadores: limites e extensão (2012 a 2016) - memórias não reveladas - Fontes, Milena Fonseca (2019)
The Truth Commissions, as well as initiatives aimed at opening political police archives, are directly linked to the realization of the right to memory and truth, in order to ensure, first, that the truth about systematic violations of humans rights that the facts of these violations are not forgotten so that they do not recur. The purpose of this paper is to identify in the final reports of truth commissions: Comissão Nacional da Verdade (CNV) Comissão da Verdade do Estado de São Paulo Rubens Paiva (CEV Rubens Paiva) and Comissão da Memória e Verdade da Prefeitura de São Paulo (CMV-SP (1964-1985), through the participation of state enterprises and apparatuses in the surveillance, monitoring, prosecution and repression of the workers and the trade union movement during the Brazilian Military Dictatorship (1964-1985). the so-called "novo regime fabril" and present the continuity of investigations after the closure of these Truth Commissions, developed by the Fórum dos Trabalhadores por Verdade, Justiça e Reparação